ANALISIS EFISIENSI PERSEDIAAN DAN MODAL KERJA PADA CV. ZAKIAH DI SANGATTA - Machmoed, Fibrianty (EKONOMIA, 2013)
Objective To determine the ability of CV . Zakiah of managing working capital efficiently to obtain profit from any sales proceeds in 2011 and in 2012 through working capital efficiency ratios . This research was motivated by the desire of the company to continue to expand its business by looking at the Vendor 's ability to carry out the procurement of goods or sales and generate profits or keuntungan.Alat analysis is the method of analysis of the efficiency ratio , or the ratio of activity covering a total asset turnover , fixed asset turnover , inventory turnover , receivables turnover , and net working capital turnover , The results of the analysis of the efficiency ratio consisting of Total Assets Turnover in 2011 spins 7.18 times increased by 0.5 times their turnaround in 2012 to 7.68 times thun . Similarly, the Fixed Assets Turnover rotates 33.8 times in 2011 rose by 2.7 times in 2012 to 36.5 times . Receivable Turover rotates 28.3 times in 2011 increased by 1.6 times in 2012 to 29.9 times . While inventory turnover in 2011 beputar 913.8 times increased by 14.8 times in 2012 to 928.6 times their turnaround . Sale of the company also experienced pengingkatan from 2011 to 2012 , Rp . 80,576,014.00 in 2011 increased by Rp . 14,875,500.00 to Rp . 95,415,514.00 in 2012 and led to an increase in the efficiency of working capital stock in 2012 than in 2011 , Rp . Nd 1,112,750.00 USD in 2012 . 545,250.00 in 2011 Total Operational net income derived from the company in 2011 amounted to U.S. $ 65,203,000.00 and in 2012 was Rp 75,715,000.00 This means net operating profit decreased by U.S. $ 10,512,000.00 dollars ) or amounted to 16.12 %